Allergic Rhinosinusitis and Airway Diseases - Duong-Quy, Sy (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Book, entiled "Allergic Rhinosinusitis and Airway Diseases", presents the concept of united airway disease interaction, which comprises chronic rhinosinusitis and other lower airway disorders such as asthma. This concept furthers a deeper comprehension on the pathophysiology and management of upper and lower airway diseases. In this Book, the published papers cover different interesting topics such as healthcare equality, advanced biomarkers, accurate diagnosis and treatment, occupational exposure-induced upper airway allergy and neoplastic disease mimicking chronic rhinosinusitis.